(untitled) (Research, Society and Development, 2022)
Thus, the objective of this study was to analyze the possibility of climatic trends using rainfall data in the Capibaribe watershed in the state of Pernambuco. A historical series of 45 years (552 months) was used between 1973 and 2018, obtained on the website of the agency Pernambucana of water and climates-APAC. The analysis was based on only one pluvimetric post. The data that presented failures were completed using the monthly averages. The Mann-Kendall test was used to identify the possibility of tendency, to detect seasonality, the Mann-Kendall seasonality test was used and in order to identify the stationary series, the KPSS tests and Dickey-Fuller. For data processing, we used the statistical software XLSTAT (version 2014.5.03) with data entry by Excel. From the Mann-Kendall test it was possible to detect that the series had no tendency, that is, the possibility of growth over time. The data remained constant. In the Pettte test, the data are homogeneous, because most of them fluctuated around the mean. It is therefore indicated that the series did not suffer local climatic variations over the period studied.